Performance and Economic Analysis of Kainji Hydropower Plant in Nigeria - Okakwu, I. K.; Alayande, A. S.; Olabode, O. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this study, performance and economic evaluation of Kainji Hydropower Station in Nigeria from 2008 to 2017 was carried out. Data including total energy generated (MWh), station service consumption (MWh), total energy sent out to the grid (MWh), average inflow rate (m3/s) and average gross operating head (m) were obtained from the efficiency department of the Hydropower station from the year 2008 to 2017. Mathematical models were used based on some key parameters which include: Capacity Factor, Plant Use Factor, Availability, Power Generated and Economic Cost of Outages and Operations. The result reveals that the average power generated within the period under review was 363.53MW, with a maximum of 476.95MW in 2010 and 292.44MW in 2014 as against the installed capacity of 760MW. The Capacity Factor of the plant was between 11.04% (2014) and 40.51% (2008) as against industry best practice of between 50% to 80%. The Plant Use Factor ranged between 38.48% in 2014 to 62.76% in 2010 as against acceptable value of 95% and above, while the plant availability hovers between 28.69% in 2015 and 91.26% in 2009 as against the recommended standard of 99.99%. The study further reveals that the revenue loss due to system downtime was ₦169,134,293,297. This revenue loss is about 66.82% of the revenue generated which is by no means a huge amount. The above values call for the need of a total overhaul of the generating plant in order to salvage the terrible state of these plants.